2012
DOI: 10.1186/1556-276x-7-490
|View full text |Cite
|
Sign up to set email alerts
|

The role of dislocation-induced scattering in electronic transport in GaxIn1-xN alloys

Abstract: Electronic transport in unintentionally doped GaxIn1-xN alloys with various Ga concentrations (x = 0.06, 0.32 and 0.52) is studied. Hall effect measurements are performed at temperatures between 77 and 300 K. Temperature dependence of carrier mobility is analysed by an analytical formula based on two-dimensional degenerate statistics by taking into account all major scattering mechanisms for a two-dimensional electron gas confined in a triangular quantum well between GaxIn1-xN epilayer and GaN buffer. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
1
9
0
2
Order By: Relevance
“…20,23 The mobility was also independent of temperature for these structures. 20 This behavior can be explained by decreased dislocation scattering. The electron mobility also decreased with In concentration from 0.1 to 0.4 in In x Ga 1Àx N. 21,22 Figure 4 shows the indium mole fraction dependence of the power loss per carrier as determined from Fig.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…20,23 The mobility was also independent of temperature for these structures. 20 This behavior can be explained by decreased dislocation scattering. The electron mobility also decreased with In concentration from 0.1 to 0.4 in In x Ga 1Àx N. 21,22 Figure 4 shows the indium mole fraction dependence of the power loss per carrier as determined from Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Electronic transport properties of In x Ga 1Àx N structures with different In concentrations have been studied by many research groups. [20][21][22][23] It has been found that the electron mobility increases with increasing In concentration from 0.48 to 0.94 in In x Ga 1Àx N structures. 20,23 The mobility was also independent of temperature for these structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, ω 0 is optical phonon frequency and G k 0 [24,25] To estimate the scattering rate, the only parameter required now is the electric field in the channel F 3 . On the basis of electrostatic analysis of the schematic conduction band profile (Figure 1) we arrived at the dependence of electric field F 3 on 2DEG density (n s ) as given by Eq.…”
Section: Estimation Of 2deg Mobilitymentioning
confidence: 99%
“…Alloy scattering (ternary materials) and dislocation scattering (GaN layer) are also considered as scatterings with defects and they are relevant in our heterostructures [62].…”
Section: Models and Measurement Techniquesmentioning
confidence: 99%